Robustness of brain state identification in synthetic phase-coupled neurodynamics using Hidden Markov Models - Pieramico, Giulia; Makkinayeri, Saeed; Guidotti, Roberto; Basti, Alessio; Voso, Domenico; Lucarelli, Delia; D’Andrea, Antea; L’Abbate, Teresa; Romani, Gian Luca; Pizzella, Vittorio; Marzetti, Laura (Frontiers in Systems Neuroscience, 2025)
Hidden Markov Models (HMMs) have emerged as a powerful tool for analyzing time series of neural activity. Gaussian HMMs and their time-resolved extension, Time-Delay Embedded HMMs (TDE-HMMs), have been instrumental in detecting discrete brain states in the form of temporal sequences of large-scale brain networks. To assess the performance of Gaussian HMMs and TDE-HMMs in this context, we conducted simulations that generated synthetic data representing multiple phase-coupled interactions between different cortical regions to mimic real neural data. Our study demonstrates that TDE-HMM performs better than Gaussian HMM in accurately detecting brain states from synthetic phase-coupled interaction data. Finally, for TDE-HMMs, we manipulated key parameters such as phase coupling variability, state duration, and influence of volume conduction effect to evaluate the models’ performance under varying conditions.